Peran Konselor Sekolah Dasar Dalam Menangani Masalah Sosial Dan Emosional Siswa Sekolah Dasar - Alwina, Sakura; Pradana Chairy Azhar; Azri Ranuwaldy Sugma (Jurnal Sintaksis, 2023)
This research explores the role of primary school counselors in dealing with students' social and emotional problems. Using a qualitative approach, the study involved in-depth interviews and participatory observation to explore the experiences and practices of counselors in two elementary schools. The findings suggest that counselors have a strategic role in detecting students' problems early, providing appropriate interventions, and preventing new problems from arising. Individual and group counseling has proven effective in helping students cope with problems, while prevention programs have a positive impact in creating a school environment that supports positive social and emotional development. Close collaboration with teachers and parents is key to providing holistic support, while the integration of social and emotional skills learning into the primary school curriculum creates an inclusive learning environment. The practical implications involve further support of counsellors with adequate training and resources. The conclusion confirms that optimizing the role of counselors in primary schools has the potential to create an educational environment that supports students' holistic development.